Development of High-Throughput Assays for Evaluation of Hematopoietic Progenitor Kinase 1 Inhibitors. (January 2021) - Lacey, Brian M.; Xu, Zangwei; Chai, Xiaomei; Laskey, Jason; Fradera, Xavier; Mittal, Payal; Mishra, Sasmita; Piesvaux, Jennifer; Saradjian, Peter; Shaffer, Lynsey; Vassileva, Galya; Gerdt, Catherine; et al.
Hematopoietic progenitor kinase 1 (HPK1), also referred to as mitogen-activated protein kinase kinase kinase kinase 1 (MAP4K1), is a serine/threonine kinase that negatively regulates T-cell signaling by phosphorylating Ser376 of Src homology 2 (SH2) domain-containing leukocyte protein of 76 kDa (SLP-76), a critical mediator of T-cell receptor activation. HPK1 loss of function mouse models demonstrated enhanced immune cell activation and beneficial antitumor activity. To enable discovery and functional characterization of high-affinity small-molecule HPK1 inhibitors, we have established high-throughput biochemical, cell-based, and novel pharmacodynamic (PD) assays. Kinase activity-based time-resolved fluorescence energy transfer (TR-FRET) assays were established as the primary biochemical approach to screen for potent inhibitors and assess selectivity against members of MAP4K and other closely related kinases. A proximal target engagement (TE) assay quantifying pSLP-76 levels as a readout and a distal assay measuring IL-2 secretion as a functional response were established using human peripheral blood mononuclear cells (PBMCs) from two healthy donors. Significant correlations between biochemical and cellular assays as well as excellent correlation between the two donors for the cellular assays were observed. pSLP-76 levels were further used as a PD marker in the preclinical murine model. This effort required the development of a novel ultrasensitive single-molecule array (SiMoA) assay to monitor pSLP-76 changes in mouse spleen.